Agenda aksi liberalisasi ekonomi dan politik di Indonesia - Ramli, Rizal; Universitas Islam Indonesia. Pusat Pengembangan Manajemen (Yogyakarta : Diterbitkan oleh Pusat Pengembangan Manajemen (PPM) FE UII bekerjasama dengan PT. Tiara Wacana Yogya, 1997)
Economic policies and political conditions, Indonesia; papers of a seminar.
Includes bibliographical references and index.
Keywords: Indonesia -- Economic policy -- Congresses; Indonesia -- Politics and government -- 1966-1998 -- Congresses